Climacteric influences for aging in the perception of elderly women: subsidies for nursing - Giuliana Fernandes e Silva; Maria Aparecida Vasconcelos Moura; Márcia Valéria de Souza Almeida; Selma Petra Chaves Sá; Ana Beatriz Azevedo Queiroz (Universidade Federal de Goias, 2015)
A qualitative, descriptive and exploratory study was conducted to analyze the influence of the climacterium on aging, in the perception of elderly women. The study was developed in the São Francisco de Assis Health Care Institute, Rio de Janeiro, Brazil. Data were collected in individual interviews with 31 women, and processed through thematic content analysis. The results showed that the climacterium, characterized by intense physical and emotional changes, influences and triggers aging, generating fear, especially for its association with approaching death. Participation in groups for the elderly brings benefits to participants, especially for socializing, new friendships, physical activity, leisure, entertainment and encouragement to better live this phase of life. In conclusion, in order to reduce the impact of the climacterium on women's lives, healthcare strategies should prioritize creative actions, based on social values, social harmony and healthy life.